Synthesis, characterization, theoretical studies and catecholase like activities of [MO6] type complexes. (21st August 2019) - Ahamad, M. Naqi; Kumar, Manjeet; Ansari, Azaj; I., Mantasha; Ahmad, Musheer; Shahid, M.
Abstract : Co(ii ) and Zn(ii ) complexes are prepared and characterized through spectral, crystallographic and theoretical studies. The Co(ii ) complex is shown to be a catechol oxidase mimic and the activity is corroborated by DFT results. Abstract : Two mononuclear complexes of Co(ii ) and Zn(ii ) with a [MO6 ] coordination sphere, [Co(L)2 (H2 O)2 ] (1 ) and [Zn(L)2 (H2 O)2 ] (2 ), are prepared and characterized through spectral, single crystal X-ray and DFT/TD-DFT studies. The X-ray structure reveals an octahedral geometry with all the oxygen donor sets around the metal ion. DFT studies confirm the cobalt complex is high spin with a +2 oxidation state. Time dependent density functional theory (TD-DFT) shows the electronic transitions to be metal to ligand (MLCT) and intra-ligand charge transfer (ILCT) type. The complexes consolidate the crystal lattice via extensive non-covalent interactions, which are verified by Hirshfeld surface analysis. These non-covalent interactions are also responsible for the enhanced DNA binding affinity of the complexes as confirmed theoretically by molecular docking studies. The Zn(ii ) complex binds to DNA with more affinity due to the lesser HOMO–LUMO energy gap calculated by DFT analysis. The complexes are assessed for catecholase like activity for oxidation of 3, 5-DTBC to 3, 5-DTBQ in ethanol.1 shows catecholase activity with the parameters K cat = 168.5 h −1, K M = 0.00043 M and V max = 4.68 × 10 −2 M min −1 . ESI-MS identifies possible intermediates formed during the catalytic cycle while EPR and cyclic voltammetry confirm the mechanism of the catalytic oxidation to be metal centered rather than radical formation. The catecholase activity of1 and inactivity of2 are also corroborated by density functional theory (DFT) analysis. The theoretical analysis results are in good agreement with the experimental findings concerning the structure, electronic spectra, DNA binding affinity and catecholase like activity. Most interestingly, the present Co(ii ) complex is discovered to be a better catecholase mimic and the activity could be tuned by modifications in the metal or structural features of the ligand(s) and complexes.